1982
DOI: 10.1111/j.1365-2818.1982.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the nature of the cryosectioning process

Abstract: Intentional melting of frozen-thin-sections induces ultrastructural alterations. Cross sections through frozen dried and embedded cryosections revealed that even at the surface of such a section no melting artefacts are visible. One surface of the cryosection (obtained at 168 K) has a saw-teeth appearance whereas the other surface is rather smooth. The rate of freeze-drying in the cryochamber of the microtome was estimated to be in order 3.3 nm/min at 183 K and 22.5 nm/min at 193 K for sections, about 120 nm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In a previous report on rat liver , we described the Wrst successful application of electron tomography to frozen-hydrated mammalian tissue. Artifacts associated with cryo-ultramicrotomy include knife marks, crevasses, chatter, and compression Chang et al, 1983;Frederik et al, 1982Frederik et al, , 1984Michel et al, 1991Michel et al, , 1992Richter et al, 1991;Richter, 1994;Zierold, 1994). Our tomographic analysis revealed that the Wrst two types of defects were predominantly conWned to the section surface, and that there was considerable useful ultrastructural information in the interior of the sections .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a previous report on rat liver , we described the Wrst successful application of electron tomography to frozen-hydrated mammalian tissue. Artifacts associated with cryo-ultramicrotomy include knife marks, crevasses, chatter, and compression Chang et al, 1983;Frederik et al, 1982Frederik et al, , 1984Michel et al, 1991Michel et al, , 1992Richter et al, 1991;Richter, 1994;Zierold, 1994). Our tomographic analysis revealed that the Wrst two types of defects were predominantly conWned to the section surface, and that there was considerable useful ultrastructural information in the interior of the sections .…”
Section: Introductionmentioning
confidence: 80%
“…the gold particles, are magniWed in the section when it is some distance from the plane of the markers. In an attempt to improve section Xatness and induce attachment, we routinely press sections onto grids with a glass section press (see Section 2) or a metal rod (Frederik et al, 1982;McDowall et al, 1983). While these procedures may Xatten the sections to some degree, results are not consistent.…”
Section: Attachment Of Frozen-hydrated Sections To Em Gridsmentioning
confidence: 99%
“…Attempts have been made to understand the sectioning process as a fracture in a solid or as a deformation in a plastic material (see Saubermann, 1980;Frederik et al, 1982). The aspect of many replicated frozen sections or block surfaces which are similar to freeze-fractured preparations supports the fracture theory.…”
Section: Cuttingmentioning
confidence: 99%
“…Currently, the methods used for creating attachment involve mechanical forces, generated by either a stamping tool or a pressing device (Christensen, 1971;Frederik et al, 1982). Using these methods for attachment, damage in the form of large fissures or cracks can be observed , which alters the integrity of both the ribbon of vitreous cryo-sections and the individual sections.…”
Section: Introductionmentioning
confidence: 99%